Some Aspects of Thermochemical Decomposition of Peat - Y. A. Losiuk; S. V. Gibric; S. V. Korchinenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper considers peculiar features of thermochemical decomposition of peat as a result of quick pyrolysis. Evaluation of energy and economic expediency of the preliminary peat decomposition process for obtaining liquid and gaseous products has been made in the paper. The paper reveals prospects pertaining to application of the given technology while generating electric power and heat.